The licensing in pedagogy in special regime of the Universidade Estadual Vale do Acaraú: Narratives of graduated teachers (Revista Contexto & Educação, 2023)
The objective was to understand how the Program for the training of pedagogical teachers in Special Regime at the Universidade Estadual Vale do Acaraú (UVA) professionally reverberated the life of lay teachers in the city of Fortaleza-CE. The temporal delimitation was from 1997 to 2004, a period that included the idealization, elaboration and execution of the program motivated both by the requirement of LDB nº 9394/96 that every teacher should graduate at a higher level to work in Basic Education, as well as by contingency of lay teachers working in the state of Ceará. It was a qualitative research, supported methodologically by the narrative research, outlined from the oralities collected through interviews, which considered for analysis the memories of three teachers from the Program under study. The results showed that the training in Special Regime meant, for the teachers, a unique opportunity to take a higher education course, in addition to professional recognition and appreciation; although it has presented weaknesses in the quality of training.
Keywords: Teacher training. Short graduation. Universidade Estadual Vale do Acaraú. Autobiographical narratives.